Strategi Pengembangan Wilayah Pesisir sebagai Perekonomian Desa Yeh Sumbul Kecamatan Mendoyo Kabupaten Jembrana - Mahendra Alfarizy (PT PUSTAKA CENDEKIA GROUP, 2025)
This research was conducted in the coastal area of Yeh Sumbul Village, Mendoyo District, Jembrana Regency with the following objectives: 1) To describe the potential coastal resources available in Yeh Sumbul Village, 2) To analyze strategies for developing the coastal area as an economic sector for the village. The methods used in this research included interviews and observations. Sampling was carried out using a purposive sampling technique. Data analysis in this research employed qualitative descriptive analysis techniques as well as SWOT analysis. The research results indicate: 1) The coastal resources in Yeh Sumbul Village include: (1) biological resources such as fisheries, lobsters, and shrimp, (2) non-biological resources that have not yet been developed, (3) artificial resources such as fishing nets, boats, and motorized boats, (4) environmental service resources such as tourism awareness groups and surfing training. 2. Strategies for developing the coastal area as an economic sector in Yeh Sumbul Village include fish farming, training to improve tourism services, providing fish collection facilities, restricting the entry of fishery products from outside the region, training the community in handicraft production, enforcing laws or awig-awig along with sanctions, and providing special funding or capital for the tourism sector.